Project-based learning: Does it improve students’ ICT literacy skills and English learning autonomy? - Menggo, Sebastianus; Ndiung, Sabina (Universitas Islam Negeri Banda Aceh, 2024)
This study aims to investigate and disclose the integration of project-based learning in promoting high school students' ICT literacy and English learning autonomy in Ruteng, Indonesia. This study surveyed 595 students from six senior high schools in Ruteng City. The questionnaire and interview served as the primary instruments for data collection, followed by quantitative and qualitative examination of the results using Jeffreys' Amazing Statistics Program. The results of the study indicate that the level of ICT literacy among the students falls in the medium category (3.5), and English learning autonomy was included in the medium category (3.32). Sixteen statements of ICT literacy competence indicated the category of ICT literacy competence, while ten items indicated English learning autonomy. In addition, five factors challenged the respondents' achievement of ICT literacy, namely, lack of enthusiasm and initiative of students regarding digital media literacy (61.59%), lack of cost of purchasing Internet data packages (71.20%), insufficient time allocated for using specific English learning software (59.48%), unstable Internet network connectivity (58.27%), and lack of available ICT infrastructure in schools (58.33%). Various issues hinder the level at which students could acquire ICT skills, and stakeholders are encouraged to address or overcome these obstacles.